Effect of matching to sample with fixed or adjusted delay on equivalence class formation - Leal, Camila Fernanda Soares; de Melo, Raquel Maria (Perspectivas em Análise do Comportamento, 2020)
The present study aimed to investigate the effect of different types of matching to sample with delay in the formation of equivalence classes with an intrasubject design. Five undergraduate students were exposed to two experimental conditions. In the Adjusted Delay Condition, the delay between the presentation of model and comparison stimuli in training increased from 1 to 1 s until reaching the maximum delay of 12 s and in the Fixed Delay Condition the delay was always 12 s. The number of trials was coupled between the experimental conditions. After the training of two conditional discriminations (AB and AC or DE and DF), with abstract visual stimuli, symmetry, transitivity and equivalence tests were performed. Results show that in Fixed Delay Condition all participants formed equivalence classes while in Adjusted Delay Condition only three. These results corroborate the literature by demonstrating that better performances are obtained after the conditional relations training with fixed delayed pairing when compared to the performances obtained after the training of conditional relations with adjusted delayed pairing.